2006
DOI: 10.1007/s00256-006-0087-3
|View full text |Cite
|
Sign up to set email alerts
|

Anaplastic large cell lymphoma presenting as an epiphyseal lytic lesion—a case report with clinico-pathologic correlation

Abstract: Anaplastic large cell lymphoma (ALCL) is predominantly a systemic disease with nodal involvement, but extranodal involvement can occur either as the primary presentation or during the disease course. Primary epiphyseal involvement is extremely rare with lymphomas. This case report illustrates an 8-year old boy who first presented with pain over the right upper extremity, which was initially treated as epiphyseal osteomyelitis. A few weeks later, he presented with abdominal pain and an abdominal wall mass, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…ALCL represents about 10-15% of NHL in children [2]. It generally arises dominal or mediastinal lymph nodes; primary bone and CNS involvement is ver After a review of English literature, we identified 17 cases of pediatric prim ALCL (Table 2) [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The median age of onset was 10 years and 82% (14/17) we Multifocal and unifocal bone lesions were identified in 7 (41%) and 10 (59%) respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ALCL represents about 10-15% of NHL in children [2]. It generally arises dominal or mediastinal lymph nodes; primary bone and CNS involvement is ver After a review of English literature, we identified 17 cases of pediatric prim ALCL (Table 2) [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The median age of onset was 10 years and 82% (14/17) we Multifocal and unifocal bone lesions were identified in 7 (41%) and 10 (59%) respectively.…”
Section: Discussionmentioning
confidence: 99%
“…After a review of English literature, we identified 17 cases of pediatric primary bone ALCL (Table 2) [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The median age of onset was 10 years and 82% (14/17) were male.…”
Section: Discussionmentioning
confidence: 99%
“…Isolated bone lymphoma was diagnosed in 3 patients (5.3%), 2 adolescents with DLBCL and a 7-year-old girl with tibial ALCL. It is extremely rare for ALCL to manifest as a primary bone lesion [22,23].…”
Section: Comprehensive Analysis Of Nhl Prevalence and Clinical Presenmentioning
confidence: 99%
“…This case report documents an epiphyseal primary lymphoma of bone, diffuse large B-cell subtype, in the left distal femur of a 13-year-old boy. This is the 5 th documented case of epiphyseal PLB, a rare diagnosis which has only been described in four other patients to date [68].…”
Section: Introductionmentioning
confidence: 96%